Analisis Teknik Copywriting dan Bahasa Iklan Digital Penerimaan Mahasiswa Baru di Instagram @Unindraofficial - Dita Rosa Utami; Mirza Agustin Rahma Putri; Siti Juriah (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to analyze copywriting techniques and language styles in digital advertisements for new student admissions published through the Instagram account @unindraofficial. In this context, the research explores three main copywriting formulas, namely AIDA, PAS, and FAB, and examines the role of diction and language style in influencing the audience. This research uses content analysis and discourse analysis methods to assess how proper language and word choices can build emotional connections with the audience and encourage them to take actions, such as registering as students. In addition, this study also applies Aristotle's rhetorical theory, which includes ethos, pathos, and logos, to evaluate credibility, emotion, and logic in advertisement texts. The findings show that the most dominant copywriting formula used is AIDA with a percentage of 90 percent, while PAS and FAB formulas appear with lower frequency and function as complements. From the linguistic aspect, the new student admission advertisements use denotative, persuasive, and emotive diction to attract attention and build engagement with prospective students. This study emphasizes that the application of appropriate copywriting techniques, effective diction, and persuasive language style plays an important role in increasing prospective students’ interest and encouraging them to register.